P253 INDEPENDENT PREDICTORS OF 1–YEAR MORTALITY IN OLDEST OLD PATIENTS MANAGED BY A GERIATRIC–CARDIOLOGY HF UNIT OF AOU CAREGGI. (18th May 2022) - Virciglio, S; Orso, F; Herbst, A; Camartini, V; Girardi, E; Ghiara, C; Perfetti, G; Pratesi, A; Di Bari, M; Ungar, A; Fattirolli, F; Marchionni, N; et al.
Abstract: Background: A multidisciplinary heart team and continuum care approach seems to be the most appropriate clinical strategy in order to reduce mortality, functional decline and disability of frail and clinical complex oldest old patients affected by heart failure (HF). We analysed the independent predictors of 1 year–total mortality in our cohort of oldest old HF patients. Methods: All patients aged > 85 years referred to our Heart Failure Unit of a Tertiary teaching hospital were consecutively enrolled in the study and were evaluated at first visit with a comprehensive assessment recording cardiological, geriatric and bio–humoral variables. Then we assessed with a multivariable Cox regression analysis the independent predictors of 1–year all–cause mortality. Results: 87 patients were enrolled (mean age 89 ± 2.7 years, range 86–96 years); 48.9% were females, 57.9% were in NYHA class III or IV, 43.2% had HFpEF, 36.4% had an ischemic aethiology, 69.3% had a history of atrial fibrillation, 19.3% were living alone, the mean number of prescribed drugs was 8.8 ± 2.2, EVEREST congestion score was 5.2 ± 2.6, mean NT–proBNP was 8187 ± 11170 pg/ml. In the year after enrolment, 25 patients (34.1%) had more than one HF hospitalisation and 17 patients (19%) died. Among all clinical variables, living alone, having had one or more HF hospitalisation and HF–type (HFpEF, HFmrEF, HFrEF), EVEREST congestion score, trans–tricuspid gradient and tricuspid annular plane systolic excursion were significantly (p < 0.05) associated with 1–year mortality. At multivariable Cox–regression model only living alone (HR 3.34; 95% CI: 1.16–9.64) and EVEREST congestion score (HR 1.24; 95% CI: 1.04–1.46) resulted significantly associated with 1–year mortality. In the Figure we report the Kaplan–Meier curves according to the EVEREST congestion score (dichotomized according to a median value of 4) and living alone (yes vs not). Conclusions: In a cohort of HF oldest old patients tightly managed in a dedicated cardiologic and geriatric Heart Failure Unit, 1–year all–cause mortality was independently predicted by a clinical score of congestion and by living alone status.